Development characteristics and controlling mechanism of different microfracture combinations in shale reservoir: A case study of Silurian Longmaxi Formation in Weiyuan area - Yuexiang Hao; Lei Wu; Wei Jiang; Chao Qian; Xin Zhou; Yuanlin Wang (Petroleum Research)
Fractures in organic-rich shale are important reservoir spaces and seepage channels of shale gas, and they are closely related to the gas-bearing properties of shale. The development characteristics and laws of fractures are of great significance in the exploration and development of shale oil and gas. This study examines organic-rich shales of the Wufeng–Longmaxi Formation in the Weiyuan area of the Sichuan Basin. On the basis of two-dimensional large-area multi-scale combination electron microscopy characterization and digital core platform technology, the development degree and distribution of different fractures are quantitatively characterized. The results show the following. (1) The shale of the Wufeng and Longmaxi formations developed a variety of fractures with different occurrences, sizes, and origins. According to the number and combination relationship between fractures of different occurrences, the shale can be divided into four fracture combination types: horizontal bedding fractures; vein fractures; reticular fractures; and ring fractures. Of these, the horizontal bedding fracture group has the largest number of samples and a higher average fracture surface porosity. (2) The degree of fracture development in the shale is affected by many factors, such as the laminar type, mineral composition, mineral particle size, mineral distribution, and total organic carbon, and the controlling mechanisms of different fracture combination types differ. Factors such as horizontal stratification, high clay mineral content, and uneven mineral particle size are conducive to the development of horizontal bedding joints. (3) Differences in the sedimentary environment affect the variation laws of the vertical fracture combination types and density. The total organic carbon and organic quartz content of the Long111 layer with deeper sedimentary water is higher, and the vein fracture formation is more developed than in other small layers, while the clay mineral content of the Long112 and Long114 layers with shallower sedimentary water is higher and the horizontal layer is more developed; the fracture combination type is dominated by the horizontal bedding fracture combination. At the same time, the fractures at the junction of each layer of the Long11 sub-member are the most developed because sea level rise and fall make the mineral particle size heterogeneity most prominent at the junction of the small layer.